Hydrological study to analyze the water budget of the Wade Gahn dam - طلال عاشور العتري و المبروك عبد القادر السنوسي و خالد ابوعجيلة راشد و انتصار محمد الغول (Journal of Pure & Applied Sciences, 2018)
Dams are usually constructed to take advantage of surface water, especially in dry and semi-dry areas. Therefore, the Wadi Gahn dam was constructed to take advantage of the valley's water for agricultural purposes and to extend water to the towns near the valley. Three decades after the construction of Wadi Gahn Dam, the water in the dam was only half the estimated volume of the lake at best. To determine the reasons for the lack of water storage, the water budget equation was used for the study area. The average precipitation of the basin as well the water losses of evaporation and infiltration were estimated and compared with previous studies of the study area. The results showed that the average annual rainfall was about 316 mm by analyzing the rainfall data for the station of the city of Gharian. The main losses of evaporation were estimated using the Benman equation for the climate parameters observed for the same station. The results showed also that the average annual evaporation was about 191 mm. The study of the water budget equation, the results showed that the lake of Wadi Gahn dam is steadily approaching the deficit in the lake of the dam due to the low rainfall and high evaporation rates.